Science-technology flows in Spanish regions: an analysis of scientific citations in patents - Daniel Coronado; Manuel Acosta (European Regional Science Association (ERSA), 2002)
Many European Regions with a high aunonomous government degree have done an effort to promote research and technological development (R&D) to achieve welfare and economic growth. In Spain several Regions have organized their efforts in science and technology, but, is really this budget effort been transferred to new technologies adopted by firms? Are science-technology flows increasing? Is there a regional gap between science and technology? Which are the factors determining these differences? In this paper we analyze the role of scientific knowledge to promote technological development in several Spanish Regions. We try to answer amongst other things, the following questions: How is the basic science used by industrial firms? Which are the most dynamic sectors using scientific knowledge? Which are the most demanded scientific fields by private firms? What type of institutions do use the scientific knowledge? Which is the lag time to translate science to technology? The used methodology to explain the link between science and technology is based on scientific inputs in patents, or non-patent citations (NPC). This paper will give an idea about science and technology links. Therefore, it is a good refference for R&D regional development future plans.
Keywords: 330